Building your investment technical toolbox - Kahn, Michael N. (FT Press Delivers elements, 2010)
"This Element is an excerpt from Technical analysis plain and simple: charting the markets in your language, third edition (ISBN: 9780137042012) by Michael N. Kahn. How to choose and use the right tool for every technical analysis task. Like quality carpentry, quality technical analysis requires the right tool for the right job. Many technicians use only a few indicators, completely ignoring some sectors of analysis. This is like building a table with two or three legs. It may stand for a while, but it won't be solid enough to deal with shifting or heavy loads"--Resource description page.